Poly (3, 4-ethylenedioxythiophene) nanoparticle as well as synthesis method and application thereof
By directly doping alkali metal or alkaline earth metal salt materials in PEDOT materials, the problems of low conductivity and poor long-term stability of PEDOT materials are solved, and PEDOT nanoparticle synthesis with high conductivity and long-term stability are achieved, suitable for flexible electrons Devices and other fields.
Patent Information
- Application Number
- CN202411684844.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The current poly(3,4-ethylenedioxythiophene) (PEDOT) materials have low conductivity and poor long-term stability, especially when exposed to air, where conductivity and optical transparency will drop rapidly.
Highly conductive PEDOT nanoparticles are synthesized by precisely controlling the reaction conditions and directly doping alkali metal or alkaline earth metal salt materials. The specific method includes dissolving the thiophene monomer in an organic solvent, adding an oxidant and a dopant, and finally obtaining PEDOT nanoparticles by filtration and washing after stirring and dropwise addition.
The conductivity of PEDOT nanoparticles is significantly improved, exceeding 550S/cm, and the long-term stability of the material in air is improved. The conductivity can still be maintained at more than 85% after 270 days. At the same time, the process is simplified, the cost is reduced, and the environmental friendliness of the materials is improved.
Smart Images

Figure BDA0005149175830000051 
Figure BDA0005149175830000061
Abstract
Description
Technical Field
[0001] The invention belongs to the field of conductive polymer materials, and in particular relates to poly(3,4-ethylenedioxythiophene) nanoparticles and a synthesis method and application thereof. Background Art
[0002] Poly(3,4-ethylenedioxythiophene) (PEDOT) is a widely used conductive polymer. Due to its unique electrical properties, mechanical flexibility and chemical stability, it has broad application potential in transparent electrodes, organic photovoltaics, flexible electronic devices and sensors. Compared with traditional conductive materials such as indium tin oxide (ITO), PEDOT has better flexibility and processability, so it shows great advantages in flexible electronic devices. However, the conductivity of unmodified PEDOT materials is relatively low (usually less than 1S / cm), which limits its application in high-performance electronic devices. In addition, the long-term stability of PEDOT in air is also a problem that needs to be solved.
[0003] In the prior art, in order to improve the conductivity of PEDOT, its electrical properties are usually enhanced by chemical doping or post-treatment technology. For example, post-treatment with acid or alkaline solution can improve the conductivity of PEDOT to a certain extent, but such methods often lead to a decrease in the stability of the material in the air, especially when exposed to a humid environment, the conductivity and optical transparency of PEDOT will decrease rapidly. In addition, traditional processing methods usually require multi-step processes, which not only increases costs, but also increases the burden on the environment.
[0004] In order to improve the application performance of PEDOT, especially to improve its conductivity and stability, researchers have developed many processing techniques. The most common way is to dope PEDOT with high boiling point solvents such as ethylene glycol or dimethyl sulfoxide (DMSO). However, although these solvents can effectively improve the conductivity, they will reduce the environmental stability of PEDOT, especially when exposed to air for a long time, the conductivity will decrease.
[0005] The synthesis of PEDOT is usually completed by oxidative polymerization. During the reaction, the conductive properties are mainly affected by the order of the polymer chain and the dopant. One way to improve the conductive properties is through post-doping or chemical modification. However, existing doping techniques such as the use of iodine vapor and nitric acid bring additional complexity and potential toxicity risks. At the same time, the use of these dopants usually reduces the stability of PEDOT in practical applications.
[0006] As environmental regulations become increasingly stringent, the demand for green and environmentally friendly synthesis methods in the chemical industry is becoming more urgent. Although the traditional process of using organic solvents for PEDOT synthesis is mature, the use of highly volatile solvents has placed a heavy burden on the environment. Therefore, the development of environmentally friendly solvent systems or low-toxicity, low-volatility chemical reagents for the synthesis and treatment of PEDOT has become a research hotspot. Summary of the invention
[0007] In view of the problems of low conductivity and poor long-term stability in the existing PEDOT synthesis technology, the purpose of the present invention is to propose a poly (3,4-ethylenedioxythiophene) nanoparticle and its synthesis method and application, and to effectively synthesize highly conductive PEDOT nanoparticles by precisely controlling the reaction conditions and directly doping alkali metal or alkaline earth metal salt materials.
[0008] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0009] The first aspect of the present invention is to provide a poly (3,4-ethylenedioxythiophene) nanoparticle, which comprises the following raw materials, by weight: 80-120 parts of an organic solvent A, 0.1-10 parts of a thiophene monomer, 10-20 parts of an oxidant, 0.5-20 parts of a dopant, and 30-80 parts of an organic solvent B; wherein the thiophene monomer is 3,4-ethylenedioxythiophene; and the dopant is selected from at least one of cesium chloride, potassium chloride, sodium chloride, lithium fluoride, calcium chloride, and magnesium chloride.
[0010] It should be noted that the thiophene monomer may also be one of the 3,4-ethylenedioxythiophene derivatives; the dopant may be selected from halides or nitrates of alkali metals or alkaline earth metals.
[0011] In some embodiments, the oxidant is selected from at least one of ferric chloride, potassium persulfate, and ammonium persulfate.
[0012] In some embodiments, organic solvent A and organic solvent B are both selected from at least one of dichloromethane and acetonitrile.
[0013] The second aspect of the present invention is to provide a method for synthesizing poly(3,4-ethylenedioxythiophene) nanoparticles, comprising the following steps:
[0014] S1: dissolving a thiophene monomer in an organic solvent A to form a solution A;
[0015] S2: dissolving the oxidant in the organic solvent B and stirring to form a B solution;
[0016] S3: adding the dopant into solution A and stirring;
[0017] S4: gradually adding solution B dropwise to the mixed system obtained in S3 and stirring;
[0018] S5: filtering the mixed solution obtained in S4 to obtain solid particles, and washing the solid particles to obtain poly(3,4-ethylenedioxythiophene) nanoparticles.
[0019] The electrical conductivity of poly(3,4-ethylenedioxythiophene) (PEDOT) molecular chains mainly depends on the order and doping state of their molecular chains. When dopants are added to the synthesis process of PEDOT, these inorganic salt dopants can interact with the positive charges in the PEDOT molecules, regulate the arrangement of the molecular chains, and thereby enhance the mobility of charge carriers, thereby effectively improving the molecular order and electrical conductivity of the material.
[0020] Inorganic salt dopants such as cesium chloride (CsCl), potassium chloride (KCl), sodium chloride (NaCl), lithium fluoride (LiF) and calcium chloride (CaCl 2 ) etc., which have a large ionic radius and can be inserted between PEDOT molecular chains to form a stable charge transfer network. Moreover, these salt materials can also interact with the groups of PEDOT to form stable ion pairs, which can effectively improve the molecular order and conductivity of the material.
[0021] In some embodiments, in S1, the reaction temperature is 0-80°C, and the solution is dissolved to form a uniform and transparent solution.
[0022] In some embodiments, in S2, the reaction temperature is 0-50°C, the stirring time is 60-120 min, and the stirring is performed until a uniform brown-red solution is formed.
[0023] In some embodiments, the reaction temperature is 0-50° C., and the stirring time is 10-60 min.
[0024] In some embodiments, in S4, the reaction temperature is 0-50°C, the stirring time is 24 hours, and the stirring is performed until a dark blue suspension is obtained.
[0025] The third aspect of the present invention is to provide an application of poly(3,4-ethylenedioxythiophene) nanoparticles in the field of flexible electronic devices, transparent conductive films or printed electronics.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The present invention is based on the effective combination of the structural characteristics of the conductive polymer poly (3,4-ethylenedioxythiophene) (PEDOT) and the doping technology, and significantly improves the conductivity of PEDOT nanoparticles by incorporating specific inorganic salt dopants (such as halides or nitrates of alkali metals and alkaline earth metals). At the same time, the inorganic salt dopants have good stability and antioxidant properties, which improves the long-term stability of the PEDOT material in the air. The addition of dopants can also promote the uniform dispersion of PEDOT nanoparticles to form a regular nanostructure, which helps to further optimize the electrical properties and optical transmittance.
[0028] 2. The present invention directly introduces these inorganic salt dopants during the synthesis process and completes the polymerization reaction of PEDOT, thus avoiding the multi-step post-processing in the traditional process, simplifying the process, reducing costs, being simple and efficient while also improving the environmental friendliness of the material.
[0029] 3. The PEDOT nanoparticles obtained by the synthesis method of the present invention not only have ultra-high conductivity (over 550 S / cm), but also have excellent long-term stability. Even after 270 days, the conductivity of the material can still maintain more than 85% of the initial value.
[0030] 4. The synthesis method provided by the present invention obtains PEDOT nanoparticles with high conductivity and high stability by regulating the reaction temperature, the type and amount of the dopant, which is suitable for a wide range of applications such as transparent electrodes, flexible displays and wearable devices. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below. The embodiments described are exemplary and intended to explain the present invention, but should not be construed as limiting the present invention.
[0032] Example 1
[0033] A poly (3,4-ethylenedioxythiophene) nanoparticle comprises the following raw materials, measured by weight: 2 parts of 3,4-ethylenedioxythiophene (EDOT), 100 parts of dichloromethane, 16 parts of ferric chloride, 50 parts of acetonitrile and 0.5 parts of cesium chloride (CsCl).
[0034] The method for synthesizing the poly(3,4-ethylenedioxythiophene) nanoparticles comprises the following steps:
[0035] S1: Dissolve 3,4-ethylenedioxythiophene (EDOT) in dichloromethane, control the reaction temperature to 25°C, and stir until a uniform and transparent solution is formed, which is called solution A.
[0036] S2: Dissolve ferric chloride in acetonitrile, control the reaction temperature at about 25°C, stir for 60 minutes, and obtain a uniform brown-red solution, called solution B.
[0037] S3: Add cesium chloride (CsCl) to solution A, control the reaction temperature to 25°C, and continue stirring for 30 minutes to make it evenly dispersed.
[0038] S4: gradually add solution B dropwise to the mixed system obtained in S3, control the dropping speed and reaction temperature (maintained at about 25° C.), continue stirring the reaction for 24 hours, and obtain a dark blue suspension.
[0039] S5: filtering the suspension after the reaction in S4 to separate solid particles, washing the solid particles with deionized water and acetone in sequence to remove impurities, and then drying to obtain highly conductive PEDOT nanoparticles.
[0040] Example 2
[0041] The raw material components and the synthesis method are the same as those in Example 1, except that cesium chloride (CsCl) is 1 part.
[0042] Example 3
[0043] The raw material components and the synthesis method are the same as those in Example 1, except that cesium chloride (CsCl) is 2 parts.
[0044] Example 4
[0045] The raw material components and the synthesis method are the same as those in Example 1, except that cesium chloride (CsCl) is 5 parts.
[0046] Example 5
[0047] The raw material components and the synthesis method are the same as those in Example 1, except that cesium chloride (CsCl) is 10 parts.
[0048] Example 6
[0049] The raw material components and the synthesis method are the same as those in Example 1, except that cesium chloride (CsCl) is 20 parts.
[0050] Example 7
[0051] The raw material components and the synthesis method are the same as those in Example 3, except that cesium chloride (CsCl) is replaced by potassium chloride (KCl).
[0052] Example 8
[0053] The raw material components and the synthesis method are the same as those in Example 3, except that cesium chloride (CsCl) is replaced by calcium chloride (CaCl 2 ).
[0054] Example 9
[0055] The raw material components and the synthesis method are the same as those in Example 3, except that cesium chloride (CsCl) is replaced by lithium fluoride (LiF).
[0056] Example 10
[0057] The raw material composition and synthesis method are the same as those in Example 3, except that cesium chloride (CsCl) is replaced by magnesium chloride (MgCl 2 ).
[0058] Comparative Example 1
[0059] The raw material components and the synthesis method are the same as those in Example 3, except that no dopant is added.
[0060] In order to verify that the poly(3,4-ethylenedioxythiophene) nanoparticles prepared by the present invention have excellent electrical conductivity and long-term stability, as well as the effect of dopants on the size and crystallinity of PEDOT nanoparticles, the PEDOT powders prepared in Examples 1 to 10 and Comparative Example 1 were subjected to electrical conductivity and crystallinity tests. The specific operation was to evaluate the electrical conductivity using a four-probe method. The test results are summarized in Table 1.
[0061] Table 1 Conductivity test and crystallinity test results
[0062]
[0063]
[0064] As can be seen from Table 1, the type and doping content of rare earth dopants have a significant impact on the conductive properties, long-term stability, nanoparticle size and crystallinity of poly(3,4-ethylenedioxythiophene) (PEDOT) nanoparticles.
[0065] First, in terms of conductivity, as the content of cesium chloride (CsCl) dopant increases, the conductivity shows a trend of first increasing and then decreasing. Specifically, when 0.5 to 2 parts of cesium chloride are doped, the conductivity gradually increases, reaching a peak of 550S / cm (2 parts of cesium chloride). However, when the doping content exceeds 5 parts, the conductivity decreases, which may be due to the destruction of the conductive network caused by excessive dopants; although the conductivity decreases, the conductivity of PEDOT with dopants is still much higher than that of PEDOT without dopants. Similarly, other dopants such as calcium chloride (CaCl 2 ), lithium fluoride (LiF), sodium chloride (NaCl), and potassium chloride (KCl) also improved the conductivity of PEDOT, but failed to achieve the optimal conductivity of cesium chloride.
[0066] In terms of long-term stability, the conductivity retention rate of each doped sample in the table after 270 days is high, generally maintained between 85% and 95%, which shows that rare earth dopants not only improve the conductivity of PEDOT, but also enhance its stability in long-term use. In particular, the samples doped with lower cesium chloride content (0.5 to 2 parts) show the highest long-term stability, with a conductivity retention rate of 95%, indicating that a more appropriate amount of doping is conducive to maintaining the long-term electrical performance stability of the material.
[0067] In terms of nanoparticle size, as the cesium chloride doping content increases, the size of the nanoparticles increases significantly. When doped with 0.5 to 2 parts of cesium chloride, the particle size is small and uniform, concentrated in the range of 50-100nm; when the dopant content increases to 10 or 20 parts, the nanoparticle size increases to 50-500nm, indicating that high concentration doping may lead to particle aggregation. In addition, the nanoparticle size generated by other rare earth metal dopants such as calcium chloride and lithium fluoride is relatively uniform, remaining in the range of 50-100nm, showing good dispersibility.
[0068] In terms of crystallinity, all doped samples showed high crystallinity, indicating that the dopant played a positive role in the orderly arrangement of PEDOT molecular chains. In contrast, the undoped comparative example 1 sample showed a semi-crystalline state, and its conductivity was significantly lower than that of the doped sample, indicating that the undoped PEDOT material had limited conductivity due to poor molecular order.
[0069] Finally, all samples in the table showed a consistent dark blue color, indicating that the addition of rare earth dopants did not significantly change the color of PEDOT nanoparticles, and all samples had a uniform appearance. This shows that rare earth doping has little effect on the optical properties of PEDOT materials, but significantly improves their electrical properties. In summary, cesium chloride doping has a particularly significant effect on the conductivity and long-term stability of PEDOT, especially when doped with 2 parts; excessive doping may cause particle aggregation and reduce conductivity. Other rare earth metals such as calcium chloride and lithium fluoride can also significantly improve conductivity and stability, but the effect is slightly inferior to cesium chloride.
[0070] The above are only some embodiments of the present invention. For those skilled in the art, several modifications and improvements can be made without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A poly(3,4-ethylenedioxythiophene) nanoparticle, characterized in that: The poly(3,4-ethylenedioxythiophene) nanoparticles include the following raw materials, by weight: 80-120 parts of an organic solvent A, 0.1-10 parts of a thiophene monomer, 10-20 parts of an oxidant, 0.5-20 parts of a dopant, and 30-80 parts of an organic solvent B; wherein the thiophene monomer is 3,4-ethylenedioxythiophene; and the dopant is selected from at least one of cesium chloride, potassium chloride, sodium chloride, lithium fluoride, calcium chloride, and magnesium chloride.
2. The poly(3,4-ethylenedioxythiophene) nanoparticles according to claim 1, characterized in that The oxidant is selected from at least one of ferric chloride, potassium persulfate and ammonium persulfate.
3. The poly(3,4-ethylenedioxythiophene) nanoparticles according to claim 2, characterized in that: The organic solvent A and the organic solvent B are both selected from at least one of dichloromethane and acetonitrile.
4. A method for synthesizing poly(3,4-ethylenedioxythiophene) nanoparticles according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: dissolving a thiophene monomer in an organic solvent A to form a solution A; S2: dissolving the oxidant in the organic solvent B and stirring to form a B solution; S3: adding the dopant into solution A and stirring; S4: gradually adding solution B dropwise to the mixed system obtained in S3 and stirring; S5: filtering the mixed solution obtained in S4 to obtain solid particles, and washing the solid particles to obtain the poly(3,4-ethylenedioxythiophene) nanoparticles.
5. The synthesis method according to claim 4, characterized in that In the S1, the reaction temperature is 0-80°C, and the solution is dissolved to form a uniform and transparent solution.
6. The synthesis method according to claim 4, characterized in that In S2, the reaction temperature is 0-50°C, the stirring time is 60-120 min, and the stirring is performed until a uniform brown-red solution is formed.
7. The synthesis method according to claim 4, characterized in that In the step S3, the reaction temperature is 0-50°C and the stirring time is 10-60 min.
8. The synthesis method according to claim 4, characterized in that In the S4, the reaction temperature is 0-50°C, the stirring time is 24 hours, and the stirring is performed until a dark blue suspension is obtained.
9. Use of the poly(3,4-ethylenedioxythiophene) nanoparticles according to any one of claims 1 to 3 in the field of flexible electronic devices, transparent conductive films or printed electronics.
Citation Information
Patent Citations
Process for synthesizing polythiophene
CN101168591A
P-type doped poly (3,4-ethylene dioxy thiophen ), preparation thereof and use
CN101307134A
Preparation method of dimeric surfactant doped PEDOT (poly(3,4-ethylenedioxythiophene)) conductive nano particle
CN102993413A
Poly (3, 4-ethylenedioxythiophene) nanoparticles and preparation method thereof
CN113372538A